2006
DOI: 10.1055/s-2006-931620
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Augmentation in Skull Base Surgery

Abstract: Objective: Skull base anatomy is complex and subject to individual variation. Understanding the complexity of surgical anatomy is faster and easier with virtual models created from primary imaging data of the patient. This study was designed to investigate the usefulness of virtual reality in image guidance for skull base procedures. Design: Primary volumetric image data from 110 patients was acquired using magnetic resonance, computed tomography (CT), and CT angiography. Pathologies included lesions in the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 20 publications
0
24
0
5
Order By: Relevance
“…Thus, there is a need for significant exposure of the surgical target and planning to safely and precisely remove the tumor. To fulfill such need, integrated systems for intraoperative surgical guidance have been actively investigated over the past several years, including systems that provide virtual and augmented reality surgical views in addition to standard planning (SP) . In analogy of the radiation oncologist outlining and contouring the target volume, virtual planning (VP) for surgical guidance requires accurate methods for anatomical contour delineation by using manual and/or automatic methods based on preoperative volumetric imaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a need for significant exposure of the surgical target and planning to safely and precisely remove the tumor. To fulfill such need, integrated systems for intraoperative surgical guidance have been actively investigated over the past several years, including systems that provide virtual and augmented reality surgical views in addition to standard planning (SP) . In analogy of the radiation oncologist outlining and contouring the target volume, virtual planning (VP) for surgical guidance requires accurate methods for anatomical contour delineation by using manual and/or automatic methods based on preoperative volumetric imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting contours can be presented to the surgeon in a 3D view for preoperative surgical planning as well for intraoperative surgical guidance. Thus, VP can help to visualize the surgical process and support the surgeon with intratreatment imaging and surgical guidance …”
Section: Introductionmentioning
confidence: 99%
“…3-D imaging has found applications in various neurosurgical fields. 1,3,[5][6][7]12,13,[15][16][17] This study showed that high-quality visualization by 3-D MFVI improved the understanding of the 3-D relationships between the tumor, important vessels, brain and CNs, and skull. We employed advanced image-analysis methods such as volume rendering to reconstruct 3-D volumetric data from a sequential 2-D dataset and image fusion to integrate multiple datasets into the same data.…”
Section: Oishi Et Almentioning
confidence: 82%
“…Further volumetric manipulation of these two-dimensional multiplanar images has refined surgical planning and navigation by producing 3D images able to delineate tumor from normal tissue and highlight vital structures through color coding. 53 These advances in preoperative imaging have been able to increase the utilization of customized hardware and reconstructive planning. This is especially true in the case of bony craniofacial surgery where computer-aided manufacturing has made it possible to precisely plan osteotomies with cutting guides and easily place prebent or custom-milled plates.…”
Section: Virtual Surgical Planningmentioning
confidence: 99%